Procedural outcomes of double vs. single fluoroscopy for fixing intertrochanteric femur fractures - Kara, Adnan; Çelik, Haluk; Şeker, Ali; Uzun, Metin; Sönmez, Mehmet Mesut; Erdil, Mehmet Emin (Springer Verlag, 2016)
Objective: This study compares reducing radiation and operation time between single and double C-arm fluoroscopy in the treatment of intertrochanteric femur fractures with intramedullary nails. Patients and methods: Forty four patients participated in the study. Patients were divided into two groups as single (23 patients) and double fluoroscope (21 patients). The time of preparation, the duration of the surgery, the total amount of blood loss, and the total duration of radiation exposure were compared, retrospectively. The collo-diaphyseal angle was compared with that of the contralateral hip on postoperative radiographs. Furthermore, the tip-apex distance and the position of the screws in the femoral head were recorded. Results: The mean preparation periods, collo-diaphyseal angles and blood loss did not differ between groups. In the double-fluoroscopy group, the duration of surgery was 15.9 min shorter (p <0.001), and the radiation time was 25.7 s shorter (p <0.001). Conclusion: The double fluoroscopy technique can significantly reduce surgical and radiation exposure times during surgery.
2016 IEEE Wireless Communications and Networking Conference, WCNC 2016 -- 3 April 2016 through 7 April 2016 -- 123767
Keywords: Double Fluoroscopy; Intertrochanteric Femur Fracture; Intramedullary Nail